Pengembangan Keamanan Dan Jaringan Pada System Windows Mengunakan Metode Hardening (Studi Kasus : PT. Shiva Shakti Steel) - Moh. Triyana Abbas; Taswanda Taryo; Murni Handayani (CV. Multi Kreasi Media, 2022)
In the current digital era, security and network are very important in a system to support all activities in the world of work, especially for offices. In this case the windows system at PT. Shiva Shakti Steel is currently still slow, supporting application performance feels slow, and network security is still vulnerable. PT. Shiva Shakti Steel is a company that uses technology and information, using the internet network on a windows system, which is expected to help management to process and present data and information effectively, quickly, and accurately. The purpose of his research is expected to accelerate the performance of the windows system, supporting applications and network security. In this study, the data analysis technique that the researcher uses is the hardening system method. Hardening system refers to providing various means of protection in a computer system. Protection is provided in multiple layers, and is often referred to as deep defense. Protecting in layers means protecting at host level, application level, operating system level. According to John D. Howard in his book